2010
DOI: 10.1111/j.1524-4725.2009.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Technical Follow-Up after Sclerotherapy

Abstract: The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Chronic venous insufficiency is a disease that affects up to one third of the population, from young adults to the elderly (1,2). Some studies (3) showed that if an active diagnostic system is used, the condition can be seen in ~2/3 of the population (1,3). There have been several suggested definitions of this condition in order to encompass both the classification and the line of treatment (1).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic venous insufficiency is a disease that affects up to one third of the population, from young adults to the elderly (1,2). Some studies (3) showed that if an active diagnostic system is used, the condition can be seen in ~2/3 of the population (1,3). There have been several suggested definitions of this condition in order to encompass both the classification and the line of treatment (1).…”
Section: Introductionmentioning
confidence: 99%